2021
DOI: 10.3390/vaccines9050490
|View full text |Cite
|
Sign up to set email alerts
|

Will COVID-19 Vaccinations End Discrimination against COVID-19 Patients in China? New Evidence on Recovered COVID-19 Patients

Abstract: (1) Background: By April 2021, over 160 million Chinese have been vaccinated against coronavirus disease 2019 (COVID-19). This study analyzed the impact of vaccination on discrimination against recovered COVID-19 patients and the determinants of discrimination among intended vaccinated people. (2) Methods: A self-designed questionnaire was used to collect data on COVID-19 associated discrimination from nine provinces in China. Pearson chi-square tests and a multivariate ordered logistic regression analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…The finding showed higher agreement on supporting compulsory vaccination when is compared to a Western Asia study which indicated only around one third of healthcare workers supporting compulsory COVID-19 vaccine for all citizens and residents [20]. However, the compulsory COVID-19 vaccination may raise legally enforceable [21] or any stigmatization or discrimination happened afterward [22]. All of these should be explored in further studies for discussion.…”
Section: Discussionmentioning
confidence: 76%
“…The finding showed higher agreement on supporting compulsory vaccination when is compared to a Western Asia study which indicated only around one third of healthcare workers supporting compulsory COVID-19 vaccine for all citizens and residents [20]. However, the compulsory COVID-19 vaccination may raise legally enforceable [21] or any stigmatization or discrimination happened afterward [22]. All of these should be explored in further studies for discussion.…”
Section: Discussionmentioning
confidence: 76%
“…There were 16 studies from Africa [ 14 , 24 , 59 , 68 73 , 75 79 , 84 , 88 ], 25 studies from Asia [ 22 , 60 , 61 , 64 66 , 74 , 80 , 81 , 83 , 86 , 87 , 90 95 , 97 – 99 , 101 , 102 , 104 , 105 ], and others were conducted in Europe [ 67 , 89 , 96 ], North America [ 62 , 63 , 85 , 100 , 103 ] and South America [ 82 ]. More than half (27 studies) of the studies were conducted within community populations [ 22 , 60 , 66 , 69 72 , 74 , 76 , 79 81 , 83 , 85 – 88 , 90 , 91 , 93 , 95 , 99 – 104 ], while others consisted of health care workers (13 studies) [ 60 , 61 , 63 , 64 , 67 , 77 , 78 , 84 , 89 , 92 , 94 , 96 , 105 ] and patients (eight studies) [ 14 , …”
Section: Resultsmentioning
confidence: 99%
“…However, as the epidemic has spread, inaccurate information about COVID-19 has become widely available and transmitted, including material that underestimates the severity of the pandemic and information that minimizes the negative repercussions of the pandemic [36] , [37] , [38] , [39] . In an effort to fight the virus, several researchers are attempting to accelerate the research and production of COVID-19 vaccinations as quickly as possible [40] , [41] , [42] . In pre-clinical research now, around 195 vaccines are being tested, with a further 144 vaccines in clinical development as of February 18, 2022 [43] .…”
Section: Related Workmentioning
confidence: 99%